Metal nanocluster light-emitting devices with suppressed parasitic emission and improved efficiency: exploring the impact of photophysical properties1. Issue 20 (28th May 2015) - Koh, T.-W.; Hiszpanski, A. M.; Sezen, M.; Naim, A.; Galfsky, T.; Trivedi, A.; Loo, Y.-L.; Menon, V.; Rand, B. P.
<x xml:space="preserve">Abstract</x> Nanoclusters with different degrees of aggregation are synthesized and their electrochemical energy levels are measured to implement light-emitting devices with luminance >40 cd m−2 and EQE >0.1%, with suppressed parasitic emission.